Biomass and Stand Characteristics of a Highly Productive Mixed Douglas-Fir and Western Hemlock Plantation in Coastal Washington - Harrison, Robert B.; Terry, Thomas A.; Licata, Christopher W.; Flaming, Barry L.; Meade, Rod; Guerrini, Iraê Amaral [UNESP]; Strahm, Brian D.; Xue, Dongsen; Lolley, M. Reese; Sidell, Amy R.; Wagoner, Gage L.; Briggs, David; et al. (Soc Amer Foresters, 2009)
Aboveground biomass predictive equations were developed for a highly productive 47-year-old mixed Douglas-fir and western hemlock stand in southwest Washington State to characterize the preharvest stand attributes for the Fall River Long-Term Site Productivity Study. The equations were developed using detailed biomass data taken from 31 Douglas-fir and 11 western hemlock trees within the original stand. The stand had an average of 615 live trees per hectare, with an average dbh of 35.6 cm (39.1 cm for Douglas-fir and 33.3 cm for western hemlock) and an average total tree height of 31.6 m (32.8 m for Douglas-fir and 30.2 m for western hemlock). Equations developed were of the form In Y = b(1) + b(2) In dbh, where Y = biomass in kg, dbh = diameter in cm at 1.3 m height, b(1) = intercept, and b(2) = slope of equation. Each tree part was estimated separately and also combined into total aboveground biomass. The total aboveground biomass estimation equations were In Y = -0.9950 + 2.0765 In dbh for Douglas-fir, and In Y = -1.6612 + 2.2321 In dbh for western hemlock. The estimate of the aboveground live-free biomass was of 395 Mg ha(-1) (235 Mg ha(-1) for Douglas-fir and 160 Mg ha(-1) for western hemlock), with 9.5, 29.3, 12.9, 308, and 32.7 Mg ha(-1) in the foliage, live branches, dead branches, stem wood, and stem hark, respectively. When compared with biomass estimates from six other studies, ranging in age from 22 to 110 years and from 96.3 to 636 Mg ha(-1), the biomass of the Fall River site was relatively high for its age, indicating very high productivity.
Keywords: prediction equations; Pacific Northwest; even-aged stands